Numerical implementation of the image filtering method with computations in Residue Number System - Nikolay Ivanovich Chervyakov; Pavel Alekseyevich Lyakhov; Diana Ivanovna Kalita; Angelina Vladimirovna Vaskina (Наука. Инновации. Технологии)
In this paper a numerical solution of the problem of digital image filtering with the use of the Residue Number System (RNS) instead of the known binary arithmetic proposes. It is substantiated that the application of the non-position RNS will allow increasing the speed and reducing power consumption of digital image processing applications. Analyzed known schemes, based on which the process of image filtration occurs. The inefficiency of the application of known schemes is substantiated, connected with the possibility of errors due to the overflow of the dynamic range of the RNS. A new scheme of the filtration transformation process is given, which allows obtaining correct results of digital processing, independent of the size of the digital image being processed and the filter mask. The obtained results can be used in the construction of specialized digital image processing systems with low power consumption and high speed of operation.